2012
DOI: 10.1063/1.4759373
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the light emission properties and carrier dynamics in dual-wavelength InGaN/GaN multiple-quantum well light emitting diodes

Abstract: Three dual-wavelength InGaN/GaN multiple quantum well (MQW) light emitting diodes (LEDs) with increasing indium content are grown by metal-organic chemical vapor deposition, which contain six periods of low-In-content MQWs and two periods of high-In-content MQWs. For the low-In-content MQWs of three studied samples, their internal quantum efficiency (IQE) shows a rising trend as the emission wavelength increases from 406 nm to 430 nm due to the suppression of carriers escape from the wells to the barriers. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…On the other hand, GaN based devices with InGaN/GaN MQWs have attracted much interest due to their wide use in optoelectronics such as LED and laser diodes. However, the green InGaN/GaN MQW LEDs are stepping into a bottleneck period because of high threading dislocations caused by lattice constants mismatch and thermal expansion coefficients between GaN based materials and substrates [104] and strong quantum stark effect (QCSE) [105]. All these can cause a heavy "efficiency droop" especially for green GaN based LEDs.…”
Section: Gan Quantum Wells Devicesmentioning
confidence: 99%
“…On the other hand, GaN based devices with InGaN/GaN MQWs have attracted much interest due to their wide use in optoelectronics such as LED and laser diodes. However, the green InGaN/GaN MQW LEDs are stepping into a bottleneck period because of high threading dislocations caused by lattice constants mismatch and thermal expansion coefficients between GaN based materials and substrates [104] and strong quantum stark effect (QCSE) [105]. All these can cause a heavy "efficiency droop" especially for green GaN based LEDs.…”
Section: Gan Quantum Wells Devicesmentioning
confidence: 99%
“…3 In c-plane InGaN/GaN LEDs, the radiative lifetimes in thicker wells are longer due to reduced overlap of electron and hole wave functions resulting from the large polarization field. 4 Liu et al 5 reported room-temperature radiative decay times as long as 686 ns in high-In-content InGaN/GaN LEDs with 3 nm thick wells, which accordingly exhibited relatively low internal quantum efficiencies (IQEs) of ~11%.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al also proposed dual-wavelength InGaN/GaN MQW LEDs, which were grown by the metal-organic chemical vapor deposition (MOCVD) with different periods of high and low indium contents. 15 Gong et al experimentally and numerically demonstrated the electrical, spectral, and optical performances of yellow-green and amber micro-pixelated InGaN LEDs to gain insight into the responsible mechanisms of dualwavelength emission. [16][17][18] Based on these researches, the properties of light-emission and dynamics of carrier transportation in the dual-wavelength InGaN/GaN MQW LEDs were further clarified.…”
mentioning
confidence: 98%
“…[21][22][23] In the redesigned structures for dual-wavelength emission, in order to achieve balanced carrier distribution and better confinement based on the experimental results provided by Lu et al and Liu et al, the five pairs of 2-nm blue QWs are divided into two pairs of 2-nm green QWs and three pairs of 6-nm violet QWs. 14,15 Due to the relatively shallow wells, the number and well width of the violet QWs are designed to be more than that of the green QWs to compensate the effect of poor carrier confinement. The schematic diagrams of the four dual-wavelength LED structures under study are depicted in Fig.…”
mentioning
confidence: 99%